Adobe Illustrator beginner - Uscilka, Deb; Safari eBooks ([Place of publication not identified] : [Intellezy], 2017)
"Adobe Illustrator is the premier drawing program used by artists and graphic designers to create vector images. In this introductory course, students will learn what Illustrator is about and when to use Illustrator. Students will learn how to use selection tools, create and save new documents, how to navigate, and how to use Adobe Bridge. In addition, students will learn how to create basic shapes, use drawing tools, master the pen tool, editing shapes, and using layers. Students will learn how to measure and transform objects, apply fills, strokes, and gradients, work with the CC libraries, and set type. Students will also learn to paint with brushes, apply special effects, and export to other file formats."--Resource description page.
Presenter, Deb Uscilka.
Title from title screen (viewed April 6, 2017).
Imprint from resource description page.
Keywords: Adobe Illustrator (Computer file); Computer graphics; Electronic books